Legal Protection for Workers with Fixed-Term Employment Agreements Before and After the Job Creation Law - Hanifah, Ida; Koto, Ismail (Universitas Muhammadiyah Purwokerto, 2025)
Workers perceive that several new provisions regarding Fixed-Term Employment Agreements are detrimental to their rights. According to research findings, an agreement is considered valid if it meets the provisions stipulated in Article 1320 of the Civil Code. The requirements for a valid agreement are regulated in Article 1320 of the Civil Code. Article 1 Paragraph (14) of Law Number 13 of 2003 concerning employment, an employment agreement is: